Wavelet Coherence as a Tool for Visualizing the Relationship between Glomerular Filtration Rate and Renal Artery Blood Flow Velocity - Wadah M. Al; Lana Haider Ahmed; Iman A Babiker; Albin Babu M Wilson; Altahir Abdalmalik Abukhiar; Garelabi M.E.M.; Hussien Abdelrhman Hussien; Mayada A. Emak; Lyashenko, V.; Mohamed M Abuzaid (WARSE, 2019)
The study of glomerular filtration rate using renal scintigraphy with enhancement and blood flow velocity in renal artery has been carried. We estimated the relationship between glomerular filtration rate and renal artery blood flow rate for each kidney and their mutual influence. To explain the results of the relationship and visualization of the research process, we used wavelet coherence. The expediency of using the wavelet methodology for conducting intellectual diagnostics for the detection of kidney diseases is shown.
Keywords: Glomerular Filtration Rate; Renal Artery Blood Flow Velocity; Kidney Diagnostics; Wavelet Analysis; Visualization; Data Mining